2011
DOI: 10.1186/1471-2261-11-57
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide and high sensitive C-reactive protein predict 2-year all cause mortality in chest pain patients: a prospective observational study from Salta, Argentina

Abstract: BackgroundSeveral mechanisms are involved in the pathophysiology of the Acute Coronary Syndrome (ACS). We have addressed whether B-type natriuretic peptide (BNP) and high-sensitive C-reactive protein (hsCRP) in admission samples may improve risk stratification in chest pain patients with suspected ACS.MethodsWe included 982 patients consecutively admitted with chest pain and suspected ACS at nine hospitals in Salta, Northern Argentina. Total and cardiac mortality were recorded during a 2-year follow up period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…The details of the ARgentinean Risk Assessment Registry in the Acute Coronary Syndrome; the “ARRA-RACS Study” (ClinicalTrial.gov   NCT01377402), have been published previously [4, 5]. Briefly, the study was performed at nine hospitals in the city of Salta, northern Argentina, including the public hospital and eight of the eleven private clinics.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The details of the ARgentinean Risk Assessment Registry in the Acute Coronary Syndrome; the “ARRA-RACS Study” (ClinicalTrial.gov   NCT01377402), have been published previously [4, 5]. Briefly, the study was performed at nine hospitals in the city of Salta, northern Argentina, including the public hospital and eight of the eleven private clinics.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary outcomes included cardiac death and SCD, as previously described [4]. Main exclusion criteria were age <18 years, unwillingness or incapacity to provide informed consent, and prior inclusion in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomarkers: Recently, from our group, Linssen et al demonstrated that plasma N-terminal pro-Brain-type natriuretic peptide (NT-proBNP) independently predicted all-cause mortality and cardiovascular events in the general population [34] . In contrast to C-reactive protein (CRP), BNP is a marker of specific pathophysiological processes, especially in relation to ventricular dysfunction and ischemic burden [35]. Many supplementary biomarkers (CRP, D-dimer, NT-proBNP) could be helpful in early diagnosis and rapid classification of acute chest pain guiding management and predicting the prognosis [36] .…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%